REVISITING MULTIMODAL DISCOURSE: A REVIEW OF INTRODUCING MULTIMODALITY (2ND EDITION, 2025) - Tran Hong Lam (Universitas Pembangunan Nasional “Veteran” Jawa Timur, 2000)
This review examines the second edition of